A Simple One‐Pot Strategy for Synthesizing Ultrafine SnS2 Nanoparticle/Graphene Composites as Anodes for Lithium/Sodium‐Ion Batteries. Issue 9 (17th April 2018) - Li, Xin; Sun, Xiaohong; Gao, Zhiwen; Hu, Xudong; Ling, Rui; Cai, Shu; Zheng, Chunming; Hu, Wenbin
Abstract: SnS2 /graphene composites have attracted extensive attention in energy storage owing to their excellent electrochemical performance. However, most of the previous methods to synthesize SnS2 /graphene composites require long times, high temperatures, or high pressures, which are obstacles for practical low‐cost production. A simple one‐pot strategy to prepare SnS2 /graphene composites has been developed, which is not time‐consuming (1 h) and requires moderate temperature (75 °C) in atmosphere. Through this method, ultrafine SnS2 nanoparticles anchored on graphene nanosheets are prepared and exhibit excellent electrochemical performance for both lithium and sodium storage. Specifically, as anodes for lithium‐ion batteries, the SnS2 /graphene electrode delivers a high capacity of 1480 mAh g −1 after 50 cycles at 0.2 A g −1 . Even at 10 A g −1, the SnS2 /graphene electrode can achieve a capacity of 666 mAh g −1 . A constructed full lithium‐ion cell exhibits a capacity of 957 mAh g −1 after 50 cycles at 1 A g −1 . This simple one‐pot strategy may pave the way for large‐scale production and practical application of SnS2 /graphene composites in energy storage. Abstract : There's nothing finer : SnS2 /graphene composites prepared by a simple one‐pot method without requiring a long time, high temperature, or high pressure exhibited excellent energy storage performance, benefitting from the combined effects of the ultrafine SnS2 nanoparticles and the graphene support.